Land use controls in local authority areas: a critique. Case study: Petaling Jaya Municipal Council and Gombak District Council / Juaina Abas Rashid - Abas Rashid, Juaina (Faculty of Architechture , Planning & Surveying, 1989)
The issue addressed in this study are of recurring interest to planners, land administrators and developers in the 19S0s.